Beyond the red horizon. - Centre for Contemporary Art Ujazdowski Castle, Warsawa; National Centre for Contemporary Arts, Moskou; Gorzadek, Ewa; Szablowski, Stach; Gorlowa, Irina (Warsaw : Centrum Sztuki Wspolczesnej Zamek Ujazdowski, 2004)
AES ; Alimpiew, Wiktor ; Baumgart, Anna ; Bakowski, Kuba ; Bratkow, Siergiej ; Czerepok, Hubert ; Bujnowski, Rafal ; Czernyszewa, Olga ; Dubosarski & Winogradow ; Program Escape ; Gomulicki, Maurycy ; Gurianow, Georgij ; et al.
Center for Contemporary Art Ujazdowski Castle, Warsaw, 29.11.2004 - 12.01.2005 / National Centre for Contemporary Arts, Moscow, 24.03 - 08.05.2005
kunstcatalogus